(untitled) (Altre Modernità, 2014)
This is not a story for people who cannot digest acronyms. Indeed, it is as if the secret services, generally considered, simply could not do without them. If, as many contend, in the term “military intelligence” resonates the echo of an oxymoron, acronyms may undoubtedly reach the practical goal of saving mental and phonetic energy, killing not less than two birds with a single stone. Applied to secret services and intelligence, acronyms fulfill a double function: they confer an indisputable aura of scientific dignity to what they aim at referring to, and they conceal behind a succession of usually eerie capital letters what they also intend to reveal.